6 - From Subalterns to Independent Actors? Youth, Social Media and the Fuel Subsidy Protests of January 2012 in Nigeria - Akor, Christopher (Africa Development, 2017)
This article explores issues around the changing nature of social networks and social movements involving youth in Nigeria. Using the youth-driven 2012 fuel subsidy protests, the article raises two fundamental questions. First, do the youth-led protests represent a genuine shift for the youth from being mere subalterns to neo-patrimonial power groups to a more assertive role, which seeks to challenge the power structure in the country, or are they simply frustrated expressions of marginality? Second, in what ways have social media affected social networks and movements and their capacity for mobilization in Nigeria? It appears that the bourgeoning youth population in Nigeria has led to a realization by youth groups of their power to substantially affect the course and conduct of governance in the country. On 1 January 2012, the Nigerian government unilaterally decided to remove the subsidy on petrol leading to a 120 per cent increase in the price of the product. The move provided opportunities for youth resistance through social media. This article uses insights from this protest to explore these questions and show the fluid nature of youth social networks and movements.